ASSESSMENT OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHS), BAP TOXICITY AND BAP-MUTAGENIC EQUIVALENTS OF CLARIAS GARIEPINUS (BURCHELL, 1822) TO NIGERIAN-PETROLEUM PRODUCTS - EZIKE, C.O; CHIDOBEM, I.J.; UWADIEGWU , N.C. (Nigerian Journal of Fisheries, 2020)
The 96-h LC50 acute toxicity and PAH levels in 720 fingerlings (0.9±0.01g) of Clarias gariepinus to various triplicate doses 1, 3, 6, 9, 12 and 0.0 ml/L (control) of crude oil, petrol, kerosene and diesel. There was no mortality in the control but 10, 20, 50 and 60% occurred in crude oil; 10, 20, 50 and 70% in petrol; 10, 20, 50 and 70% in kerosene and 10, 20, 30, 40 and 60% in diesel respectively at 1, 3, 6, 9 and 12 ml/L after 96 hour exposure. The logarithmic probit lines and R2: y = 1.372x + 3.724, R² = 0.997; y = 1.665x + 3.694, R² = 0.998; y = 1.665x + 3.694, R² = 0.998 and y = 1.665x + 3.694, R² = 0.998 and 96-h LC50: 9.6, 6.98, 6.2 and 11.0ml/L represented toxicity values for crude oil, petrol, kerosene and diesel to C. gariepinus. Total pah value of petroleum products in exposed fish ranged from highest value of 99.68±4.81 crude oil > 97.30± 14.57 diesel oil > 35.413±0.90 petrol > 32.72±3.60 ng/µL kerosene. The lowest value of 0.061 was shown in Nap while highest value was 384.68 in DahA >383.47 B[ghi] P > 361.38 IP >236.41BaA >71.59 BbF>60.17 BkF >37.17 BaP> 22.82FI> 17.72A >5.33Chry >4.56 Flu> 4.35 Phe>2.79 Acy>2.40Ace >0.06Nap for crude oil. The sequence in petrol indicate highest value of 95.45BaA >94.50 IP>89.61 B[ghi] P >83.67 DahA>72.46 BkF>50.65BbF >44.69 BaP>13.19 FI>11.57 Chry>5.67 A>2.78 Phe>2.56Flu for petrol. In kerosene, the sequence from highest level of 91.56 BaA>90.69 IP> 77.96 BkF>75.99 B[ghi] P >49.55 BbF>41.31 BaP>11.34 FI>9.11 Chry>6.63 A>2.48 Phe>1.97Flu. Diesel oil however indicated highest value of 389.05DahA> 355.70 B[ghi] P >343.48 IP>262.80 BaA>65.35 BbF>58.16 BkF>30.38 BaP>20.09 FI>18.48 A>4.79 Chry>3.79 Phe>2.51 Acy>2.22. Mean ∑ 16PAH of lighter products showed greater toxicity than heavier products due to greater level of BaA - BaP compared to DahA- BaP. On the other hand, heavier petroleum with greater total mean ∑ 8PAH was more carcinogenic and mutagenic compared to lighter petroleum.